Composite paraganglioma-ganglioneuroma of the urinary bladder: a rare neoplasm causing hemodynamic crisis at tumour resection - Chen, C-H.; Boag, Alexander H.; Beiko, Darren T.; Siemens, Robert; Froese, Alison; Isotalo, Phillip A. (Canadian Urological Association Journal, 2013)
A 64-year-old man presented with gross painless hematuria. Cystoscopy revealed a submucosal bladder neck mass covered by normal urothelium. During transurethral resection, the patient developed hemodynamic crisis including sinus bradycardia. Histopathologic examination revealed a primary bladder composite paraganglioma-ganglioneuroma (CPG). The patient underwent partial cystectomy and is symptom-free after one year. Bladder CPGs are extremely rare neoplasms that may result in lifethreatening catecholamine secretion, especially during tumour manipulation. These tumours require complete surgical excision and should be included in the differential diagnosis of any solitary bladder mass covered by normal urothelium, especially when there is a history of hypertension or micturition attacks.